Computational studies on the interactions of inhalational anesthetics with proteins. - Vemparala, S; Domene, C; Klein, M (2010)
Despite the widespread clinical use of anesthetics since the 19th century, a clear understanding of the mechanism of anesthetic action has yet to emerge. On the basis of early experiments by Meyer, Overton, and subsequent researchers, the cell's lipid membrane was generally concluded to be the primary site of action of anesthetics. However, later experiments with lipid-free globular proteins, such as luciferase and apoferritin, shifted the focus of anesthetic action to proteins. Recent experimental studies, such as photoaffinity labeling and mutagenesis on membrane proteins, have suggested specific binding sites for anesthetic molecules, further strengthening the proteocentric view of anesthetic mechanism. With the increased availability of high-resolution crystal structures of ion channels and other integral membrane proteins, as well as the availability of powerful computers, the structure-function relationship of anesthetic-protein interactions can now be investigated in atomic detail. In this Account, we review recent experiments and related computer simulation studies involving interactions of inhalational anesthetics and proteins, with a particular focus on membrane proteins. Globular proteins have long been used as models for understanding the role of protein-anesthetic interactions and are accordingly examined in this Account. Using selected examples of membrane proteins, such as nicotinic acetyl choline receptor (nAChR) and potassium channels, we address the issues of anesthetic binding pockets in proteins, the role of conformation in anesthetic effects, and the modulation of local as well as global dynamics of proteins by inhaled anesthetics. In the case of nicotinic receptors, inhalational anesthetic halothane binds to the hydrophobic cavity close to the M2-M3 loop. This binding modulates the dynamics of the M2-M3 loop, which is implicated in allosterically transmitting the effects to the channel gate, thus altering the function of the protein. In potassium channels, anesthetic molecules preferentially potentiate the open conformation by quenching the motion of the aromatic residues implicated in the gating of the channel. These simulations suggest that low-affinity drugs (such as inhalational anesthetics) modulate the protein function by influencing local as well as global dynamics of proteins. Because of intrinsic experimental limitations, computational approaches represent an important avenue for exploring the mode of action of anesthetics. Molecular dynamics simulations-a computational technique frequently used in the general study of proteins-offer particular insight in the study of the interaction of inhalational anesthetics with membrane proteins.